Low seasonal variation in greater mouse-eared bat (Myotis myotis) blood parameters - Bandouchova, Hana (PLoS One, 2020)
The greater mouse-eared bat (Myotis myotis) is a flagship species for the protection of hibernation and summer maternity roosts in the Western Palearctic region. A range of pathogenic agents is known to put pressure on populations, including the white-nose syndrome fungus, for which the species shows the highest prevalence and infection intensity of all European bat species. Here, we perform analysis of blood parameters characteristic for the species during its natural annual life cycle in order to establish reference values. Despite sexual dimorphism and some univariate differences, the overall multivariate pattern suggests low seasonal variation with homeostatic mechanisms effectively regulating haematology and blood biochemistry ranges. Overall, the species displayed a high haematocrit and haemoglobin content and high concentration of urea, while blood glucose levels in swarming and hibernating bats ranged from hypo- to normoglycaemic. Unlike blood pH, concentrations of electrolytes were wide ranging. To conclude, baseline data for blood physiology are a useful tool for providing suitable medical care in rescue centres, for studying population health in bats adapting to environmental change, and for understanding bat responses to stressors of conservation and/or zoonotic importance.